2010
DOI: 10.1007/s10228-010-0174-2
|View full text |Cite
|
Sign up to set email alerts
|

Life history and migration of Sakhalin taimen, Hucho perryi, caught from Lake Akkeshi in eastern Hokkaido, Japan, as revealed by Sr:Ca ratios of otoliths

Abstract: Microchemical analysis of the strontium (Sr) and calcium (Ca) ratios of otoliths was conducted to determine the life history and migration of anadromous Sakhalin taimen, Hucho perryi. In 2008 and 2009, 10 specimens were sampled from Lake Akkeshi in eastern Hokkaido, Japan. Our results indicated that some specimens migrated to brackish waters during their early life history. Because the Sr:Ca ratios of the specimens in this study were all less than those of specimens from Sakhalin Island during a previous study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
(26 reference statements)
4
17
0
Order By: Relevance
“…In combination, otolith microchemistry has been used to describe migratory behavior in only a total of 31 Sakhalin taimen: 13 in this study, eight in Arai et al (2004), and ten in Honda et al (2010). These results suggest that there are existing gaps in our knowledge of taimen behavior and ecology.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In combination, otolith microchemistry has been used to describe migratory behavior in only a total of 31 Sakhalin taimen: 13 in this study, eight in Arai et al (2004), and ten in Honda et al (2010). These results suggest that there are existing gaps in our knowledge of taimen behavior and ecology.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggest that there are existing gaps in our knowledge of taimen behavior and ecology. It is clear that diadromous migrations are conducted by Sakhalin taimen (Arai et al 2004;Honda et al 2010), but it is not clear whether these migrations are annual (as observed in amphidromous species such as Dolly Varden Salvelinus malma; Armstrong 1974), or if taimen overwinter in seawater. Further, it is not clear what proportion of Sakhalin taimen are diadromous and how that proportion is controlled by watershed and estuarine productivity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, information about the life history of anadromous Sakhalin taimen is still limited with only a few studies being done on ecological aspects of their freshwater phases [8][9][10][11], the morphology of anadromous Sakhalin taimen [12], or on the microchemistry of the otoliths and scales [13][14][15]. Fish otoliths are metabolically inert with the aragonite mineralogy remaining unaltered after deposition [16], so the elemental composition of the otolith reflects to some degree the environment of the water in which the fish lives [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other numbers stand for Sakhalin taimen populations: 1 Piltun Bay, 2 Val River, 3 Dagi River, 4 Tym River, 5 Nabil River, 6 Langeri River, 7 Poronay River and its tributaries (8 Onorka, 9 Brusnichnaya, 10 Elnaya), 11 Nevskoe Lake, 12 Tunaicha Lake, 13 Vavaiskoe Lake, 14 Urjum River, 15 Uljanovka River, 16 Moguchi River, 17 Lebedinoe Lake, 18 Kuibyshevka River, 19 Valentina Lake, 20 Sarafutsu River, 21 Tainoe Lake, 22 Ainskoe Lake, 23 Agnevo River, 24 Viakhtu River and Viakhtu Bay, 25 Tyk Bay, 26 Ulika River, 27 Tumnin River, 28 Koppi River, 29 Samarga River, 30 Kievka River characterized the species as semi-anadromous assuming that they do not migrate far from the natal river mouth. The strontium-to-calcium ratio in their otoliths can help recognize anadromous versus non-anadromous behaviors (Edo et al 2005;Honda et al 2010;Zimmerman et al 2012), but this method requires sacrificing individual fish.…”
Section: Assignment Into Migratory Phenotypesmentioning
confidence: 99%